2021
DOI: 10.1177/17085381211025152
|View full text |Cite
|
Sign up to set email alerts
|

The use of the Amplatzer Vascular Plug in the prevention of endoleaks during abdominal endovascular aneurysm repair: A systematic literature review on current applications

Abstract: Objectives The Amplatzer Vascular Plug (AVP) is a vascular occlusion device designed to provide optimal embolization in several fields of the endovascular surgery. A full literature review was conducted to analyze AVPs in comparison with coils for the prevention of endoleaks during endovascular abdominal aortic aneurysm repair. Methods A systematic review was designed under PRISMA statement guidelines for systematic reviews and meta-analyses. The results were updated with a subsequent electronic search using M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Exclusion of RAA through stents and embolization is characterized by success rates of 73%-100% and variable complication rates of 13%-60%. As well, embolization with coils, onyx or plugs can be used to reduce risk of bleeding as a prior step to open surgery or as a useful combined 1 step therapeutic strategy [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion of RAA through stents and embolization is characterized by success rates of 73%-100% and variable complication rates of 13%-60%. As well, embolization with coils, onyx or plugs can be used to reduce risk of bleeding as a prior step to open surgery or as a useful combined 1 step therapeutic strategy [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] .…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, plugs seem to be safer than coils in achieving complete occlusion with lower rates of complications as it has been reported that plugs have lower rates of buttock claudication and erectile dysfunction [50,51]. When the sealing zone length is scarce, a short plug such as the AVP should be preferred to a longer plug such as the AVPII, which is chosen in cases of normal length [52]. Proximal positioning of the plug must be avoided in case of aneurysmatic IIA, in which cases the backflow through terminal branches could promote sac enlargement in the IIA.…”
Section: Internal Iliac Artery (Iia)mentioning
confidence: 99%
“…Various mechanical devices are available for endovascular embolization, such as septal occluders, coils, and vascular plugs. Amplatzer™ Vascular Plugs (AVPs) (Abbott Medical, Plymouth, MN, USA) are self-expanding nitinol devices which can be used for a wide range of acquired and congenital diseases [1][2][3][4][5][6][7]. Configuration and characteristics of these devices are well described [4,8].…”
Section: Introductionmentioning
confidence: 99%